2002
DOI: 10.1097/00075197-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the assessment of dietary intake: problems of misreporting

Abstract: Campaigns aimed at changing food intake might not be as successful as concluded from the results of national food consumption measurements. Subjects might be reporting according to expected instead of real intake. In a clinical setting, the increased awareness of the nursing staff has been observed to result in overreporting of intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
186
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(193 citation statements)
references
References 27 publications
4
186
0
3
Order By: Relevance
“…The results suggest that the shorter SDQ is as accurate as a traditionally designed and more extensive FFQ in estimating EI, nutrients and foods. There has been some discussion about whether women generally under-report more than men, but evidence points to no consistent differences in reporting accuracy between the sexes (4,25,26) . However, a number of previous validation studies of FFQ in women have reported underestimation of EI when compared with TEE measured by the DLW method (5,6,26,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that the shorter SDQ is as accurate as a traditionally designed and more extensive FFQ in estimating EI, nutrients and foods. There has been some discussion about whether women generally under-report more than men, but evidence points to no consistent differences in reporting accuracy between the sexes (4,25,26) . However, a number of previous validation studies of FFQ in women have reported underestimation of EI when compared with TEE measured by the DLW method (5,6,26,27) .…”
Section: Discussionmentioning
confidence: 99%
“…The FFQ method is most often used in epidemiological studies (1) , since it is easy to administer at a relatively low cost and estimates habitual dietary intake over an extended time period (2) . A valid FFQ can be used to rank individuals according to reported intake and, if it includes portion size estimations, to assess absolute individual intakes (3) .However, a problem with all self-report dietary assessment methods is the misreporting of energy intake (EI) (4) . Dietary intake in young, weight-conscious women can be especially difficult to assess accurately, and previous studies in women show underestimation of EI when assessed using FFQ by comparison with total energy expenditure (TEE) measured by the doubly labelled water (DLW) method (5,6) .…”
mentioning
confidence: 99%
“…A small pilot study to test a fish consumption questionnaire containing detailed and summary questions also found that an aggregate overestimated fish consumption relative to a summary measure 14 . This is of practical importance given that studies comparing estimated intakes with biomarkers of energy have demonstrated a tendency for FFQs and food records to typically underestimate consumption 15,16 . This underestimation could be amplified by the use of abbreviated questioning, and has implications for the usefulness of dietary estimates collected by abbreviated FFQs for the purpose of examining associations between absolute dietary intakes and disease.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 When this method was used to compare self-reported energy intakes with energy expenditure, it became clear that energy intake was often considerably underestimated, due to a combination of underrecording and temporary undereating. 26,27 Importantly, the degree of underestimation of intake was positively related to the BMI of the subjects. Consequently, dietary surveys cannot be used for drawing conclusions on dietary intake over time, or for comparing lean to obese subjects.…”
Section: Introductionmentioning
confidence: 98%